Nitrogen Uptake Rates during Spring in the NE Arabian Sea. (27th September 2010) - Gandhi, Naveen; Ramesh, R.; Srivastava, R.; Sheshshayee, M. S.; Dwivedi, R. M.; Raman, Mini
Abstract : We present new data on N uptake rates and f -ratios in the north-eastern (NE) Arabian Sea, where significant amounts of Trichodesmium were present in spring, 2006. The measured total nitrogen uptake rates ranged from 0.34 to 1.58 mmol N m − 2 d − 1 .N 2 fixation associated with Trichodesmium varied from 0.002 to 0.54 mmol Nm − 2 d − 1 estimated from the abundance of Trichodesmium and specificN 2 fixation rates of 1.5 pmol N trichome − 1 h − 1 . Inclusion ofN 2 fixation rates significantly changes f -ratios particularly in the coastal stations. Nitrogen isotopic data of surface suspended particles suggest that recently fixed nitrogen contributes as high as 79% of the nitrogen in surface suspended particles. In addition, water column gained 30 mmol Nm − 2 in the form of nitrate, likely due to nitrification of ammonium released by Trichodesmium . For better estimations, direct measurement ofN 2 fixation is recommended.